2023
DOI: 10.3390/s23094486
|View full text |Cite
|
Sign up to set email alerts
|

Towards Preventing Gaps in Health Care Systems through Smartphone Use: Analysis of ARKit for Accurate Measurement of Facial Distances in Different Angles

Abstract: There is a growing consensus in the global health community that the use of communication technologies will be an essential factor in ensuring universal health coverage of the world’s population. New technologies can only be used profitably if their accuracy is sufficient. Therefore, we explore the feasibility of using Apple’s ARKit technology to accurately measure the distance from the user’s eye to their smartphone screen. We developed an iOS application for measuring eyes-to-phone distances in various angle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…Nissen et al proposed an application to estimate the eye-to-phone distance from different angles using ARKit. 9 Various experimental results confirmed that ARKit is capable of producing accurate distance measurements across various face poses. Mobile applications have also played an important role in helping health professionals taking better photos in various settings.…”
Section: Related Workmentioning
confidence: 73%
“…Nissen et al proposed an application to estimate the eye-to-phone distance from different angles using ARKit. 9 Various experimental results confirmed that ARKit is capable of producing accurate distance measurements across various face poses. Mobile applications have also played an important role in helping health professionals taking better photos in various settings.…”
Section: Related Workmentioning
confidence: 73%
“…Although time can be measured without an eye-tracker, the iPad can still offer a lot in the way of ensuring participant compliance. For example, in scenarios where the stimulus size (in visual degrees) must remain constant, the iPad can accurately measure the participant's distance from the device ( Nissen et al., 2023 ). Despite its modest accuracy, the iPad eye-tracking system can also estimate instances when the participant turns completely away from the screen.…”
Section: Discussionmentioning
confidence: 99%